PERAN MAHASISWA SEBAGAI AGEN PERUBAHAN DALAM MENJAGA KEAMANAN TINDAK KEJAHATAN PENCURIAN DI LINGKUNGAN KAMPUS - Milani Nabila Syahra; Edy Soesanto, Yesa Privi Azahra, Nabilah Helya Diana (ADISAM PUBLISHER, 2023)
To find out the role of students in the security of the campus environment and find out the factors that cause security and comfort in the campus environment. This research method uses qualitative research with a case study approach which aims to obtain a picture of the actual situation at the location through collecting existing data. Based on research results, students play an important role as agents of change and social control in social life, especially in the campus environment. Students as agents of change must be able to champion changes in the security of the campus environment. Therefore, in this case, students as agents of change can make changes by going directly into the community to help solve various social problems faced by society, especially in the campus environment. and also from the results of our research we found efforts to maintain campus security from acts of theft, namely that security guards can give warnings and carry out controls every day, and security guards can also take action if the perpetrator of the theft is known to have committed theft and the perpetrator is caught by the security guard. Apart from security guards, students also play an important role in maintaining the security of the campus environment, but in reality students lack awareness in maintaining campus security. The security guard's job in protecting the campus environment will run well if there is good cooperation with students so that they can maintain campus security and as a last resort, the campus can also install more CCTV so that the perpetrators feel free to carry out their mission.